Blood is Your Bond: Newspaper Perceptions of Lineage Complications in Ghana - Heib, Lauren (The Toro Historical Review, 2025)
In 1821, the Gold Coast became a British colony, bringing change to Ghana's social, political, and economic structure. By 1918, British ideologies had infiltrated even the most intimate parts of Ghanaian life and thus impacted marriage, inheritance, and household gender roles. In the Gold Coast, inheritance was matrilineal, meaning that inheritance was passed down through the mother’s blood line and children belonged to the mother’s family, or Abusua. However, that did not mean that this practice benefited women. As the colonial government altered both the economy and gender roles, wives labor became subservient to their husbands and their unpaid labor became their husbands’ benefit. In response, Ghanaian women enacted new measures to ensure wealth for themselves and their Abusua. By the late 1950s, matrilineal inheritance was a longstanding Ghanaian tradition, withstanding the new European marriage practices and legalities. Despite this longevity, matrilineal inheritance began to encounter challenges regarding its efficiency. By examining Ghana's independence period and subsequent aftermath, we can see how Ghanaian women reclaimed their autonomy by demanding land independent from their husbands, refusing to marry, or challenging their husbands Abusua in colonial courts for a share in their husband’s land. Furthermore, as women challenged colonial authority for rights over their labor, and in return, men demanded more ownership of their children. Through the use of newspaper articles, published in Ghana's Daily Graphic, we can observe the argument for and against matrilineal inheritance, and how Ghanaians challenged colonial influence as Ghana approached independence.